Acute cardiac support with intravenous milrinone promotes recovery from early brain injury in a murine model of severe subarachnoid haemorrhage. (April 2017) - Mutoh, Tomoko; Mutoh, Tatsushi; Nakamura, Kazuhiro; Yamamoto, Yukiko; Tsuru, Yoshiharu; Tsubone, Hirokazu; Ishikawa, Tatsuya; Taki, Yasuyuki
Summary: Early brain injury/ischaemia (EBI) is a serious complication early after subarachnoid haemorrhage (SAH) that contributes to development of delayed cerebral ischaemia (DCI). This study aimed to determine the role of inotropic cardiac support using milrinone (MIL) on restoring acute cerebral hypoperfusion attributable to EBI and improving outcomes after experimental SAH. Forty‐three male C57BL/6 mice were assigned to either sham surgery (SAH‐sham), SAH induced by endovascular perforation plus postconditioning with 2% isoflurane (Control), or SAH plus isoflurane combined with MIL with and without hypoxia‐inducible factor inhibitor (HIF‐I) pretreatment. Cardiac output (CO) during intravenous MIL infusion (0.25‐0.75 μg/kg/min) between 1.5 and 2.5 hours after SAH induction was monitored with Doppler echocardiography. Magnetic resonance imaging (MRI)‐continuous arterial spin labelling was used for quantitative cerebral blood flow (CBF) measurements. Neurobehavioral function was assessed daily by neurological score and open field test. DCI was analyzed 3 days later by determining infarction on MRI. Mild reduction of cardiac output (CO) and global cerebral blood flow (CBF) depression were notable early after SAH. MIL increased CO in a dose‐dependent manner ( P <.001), which was accompanied by improved hypoperfusion, incidence of DCI and functional recovery than Control ( P <.05). The neuroprotective effects afforded by MIL or Control were attenuated by hypoxia‐inducible factor (HIF) inhibition ( P <.05). These results suggest that MIL improves acute hypoperfusion by its inotropic effect, leading to neurobehavioral improvement in mice after severe SAH, in which HIF may be acting as a critical mediator.